Alum Adjuvant and Built-in TLR7 Agonist Synergistically Enhance Anti-MUC1 Immune Responses for Cancer Vaccine - Zhou, Shi-Hao; Li, Yu-Ting; Zhang, Ru-Yan; Liu, Yan-Ling; You, Zi-Wei; Bian, Miao-Miao; Wen, Yu; Wang, Jian; Du, Jing-Jing; Guo, Jun (Frontiers in Immunology, 2022)
The tumor associated antigen mucin 1 (MUC1) is an attractive target of anti-tumor vaccine, but its weak immunogenicity is a big challenge for the vaccine development. In order to enhance immune responses against MUC1, herein we conjugated small molecular toll-like receptor 7 agonist (TLR7a) to carrier protein BSA via MUC1 glycopeptide to form a three-component conjugate (BSA-MUC1-TLR7a). Furthermore, we combined the three-component conjugate with Alum adjuvant to explore their synergistic effects. The immunological studies indicated that Alum adjuvant and built-in TLR7a synergistically enhanced anti-MUC1 antibody responses and showed Th1-biased immune responses. Meanwhile, antibodies elicited by the vaccine candidate effectively recognized tumor cells and induced complement dependent cytotoxicity. In addition, Alum adjuvant and built-in TLR7a synergistically enhanced MUC1 glycopeptide-specific memory CD8+ T cells immune responses. More importantly, the vaccine with the binary adjuvant can significantly inhibit tumor growth and prolong the survival time of mice in the tumor challenge experiment. This novel vaccine construct provides an effective strategy to develop anti-tumor vaccines.